Changes in ectocervical surface area in women throughout pregnancy compared to non-pregnant and postpartum states. (16th November 2016) - Qian, Xueya; Jiang, Yanmin; Liu, Lei; Shi, Shao-qing; Garfield, Robert E.; Liu, Huishu
Abstract: Objective : The objective of this study is to estimate changes in the surface area of the ectocervix (CA) in women during pregnancy and compare this to postpartum and non-pregnant states. Methods : CA was evaluated in 210 normal nulliparous women divided into groups from early to late gestation, 40 postpartum women, and 25 non-pregnant women. CA in cm 2 was estimated from analysis of images taken with an endoscope of the cervical face and an mm scale. An mm scale was also used to determine fornix length and fornix area computed. Results : The face, fornix, and total areas of the CA of non-pregnant and postpartum groups are significantly smaller ( p < 0.001) than these areas in groups during pregnancy. Generally, the CA of the face, fornix, and total area are also less in early pregnancy compared with late gestation ( p < 0.01 to <0.001). Total CA correlates with gestational age ( r = 0.196, p < 0.004). Conclusions : (1) During pregnancy, CA slowly and progressively increases to >75% area compared with CA of non-pregnant patients and then reverts back to low CA postpartum. (2) Increases in CA during pregnancy occur in both the face and fornix areas. (3) Increases in CA reflect enlargement in cervical volume and remodeling during pregnancy.